Becoming aware of the role of OCB in determining the relationship between HRM practise and performance: Evidence from social enterprise - Realita, Tasnim Nikmatullah; Pratikto, Heri; Wardoyo, Cipto; Hermawan, Agus (Journal of Social Economics Research, 2023)
The purpose of this study was to examine the influence of human resource management (HRM) practice variables on performance, with organizational citizenship behavior (OCB) as a mediating variable. This research specifically uses social enterprise as study material due to the different characteristics of social enterprise from other organizations in terms of organizational governance, where commercial logic and social logic are combined. This study uses a quantitative approach, involving 100 worker respondents in social enterprises in a survey, to see the influence of HRM practice variables on organizational performance with OCB as a mediator. Based on the results of data analysis using SEM-PLS, it was found that HRM practices have a significant effect on organizational performance. When the OCB mediates this influence, it is well known to be even stronger. The study's findings practically affect how human resource policies are decided since they suggest that practices should be created to encourage workers to perform to their highest potential.